Intersecting Structural Oppression and Suicidality Among Black Sexual Minority Male Adolescents and Emerging Adults. (15th February 2022) - English, Devin; Boone, Cheriko A.; Carter, Joseph A.; Talan, Ali J.; Busby, Danielle R.; Moody, Raymond L.; Cunningham, Diamond J.; Bowleg, Lisa; Rendina, H. Jonathon
Abstract : This study examined associations between structural racism, anti‐LGBTQ policies, and suicide risk among young sexual minority men (SMM). Participants were a 2017–2018 Internet‐based U.S. national sample of 497 Black and 1536 White SMM (ages 16–25). Structural equation modeling tested associations from indicators of structural racism, anti‐LGBTQ policies, and their interaction to suicide risk factors. For Black participants, structural racism and anti‐LGBTQ policies were significantly positively associated with depressive symptoms, heavy drinking, perceived burdensomeness, thwarted belongingness, self‐harm, and suicide attempt. There were significant interaction effects: Positive associations between structural racism and several outcomes were stronger for Black participants in high anti‐LGBTQ policy states. Structural racism, anti‐LGBTQ policies, and their interaction were not significantly associated with suicide risk for White SMM.